“Melhores mestres...”: saberes indígenas e ciência colonial no vale Amazônico (século XVIII) - SANTOS, Rafael Rogério Nascimento dos (Universidade Federal do Pará, 2024)
This thesis analyzes the roles that the indigenous peoples of the Amazon Valley played in the circulation/construction of knowledge during the second half of 18th century, considering them as subjects who were actively involved in this process, as historical protagonists. From the perspective of Indigenous History and the History of Science, and through documentation, I demonstrate that their knowledge was part of the constitution of the natural sciences under construction in that period, and how, to a considerable extent, their knowledge was appropriated by the modern science under construction at the time. The thesis states that the construction of knowledge, as well as its circulation, relied essentially on local sources and practices, and, as I try to show and analyze, on indigenous practices, techniques and knowledge. I present and analyze sources that make it possible to insert the indigenous peoples of the Amazon Valley into the history of Western scientific knowledge.